Synthesis of random and block copolymers from terpene-based and acrylate-based monomers - Jordan, Beth (2022)
Due to the ever-growing need to reduce global carbon emissions , the need to replace traditionally petrochemically derived plastics has been growing exponentially. To solve this issue, research has been carried out on plant-based alternatives such as terpenes and terpenoids. Terpenes are a type of natural hydrocarbon which contains a carbon-carbon double bond which can be exploited for polymerisations. Many polymerisation reactions are also carried out in toxic and petrochemical based solvents, in order to reduce the environmental impact of these reactions, bio-based solvents have become a viable alternative.